Comparison of the Effectiveness of Aerobic Gymnastics and Zumba on Increasing VO₂ Max of the Gymnastics Team Community at CPI Makassar City - Retno Farhana Nurulita (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
Increasing cardiovascular capacity is an important aspect in maintaining public health, especially through community-based physical activity. This study aims to compare the effectiveness of aerobics and zumba on increasing VO₂ max in the gymnastics team community at CPI Makassar City. Using a quasi-experimental method with a Non-Equivalent Control Group design, 30 community members were divided into two treatment groups. Data collection was carried out through pre-test and post-test measurements using the Balke Test, and data analysis was carried out using paired t-test, independent t-test, and two-way ANOVA. The results of the independent t-test on the delta increase in VO₂ max showed that the zumba group experienced a statistically greater increase than the aerobic group, with a t value = -5.26 and p = 1.35 × 10⁻⁵ (p <0.05). These findings reinforce that music-based activities and dynamic movements such as zumba are more effective in increasing the aerobic capacity of the general public. This study provides an important contribution to developing evidence-based community fitness programs and leads to the development of more effective interventions to improve cardiovascular health. Future studies are recommended to involve larger samples with full experimental designs.